2009
DOI: 10.1097/bot.0b013e3181a18198
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Fine Wire Fixation and Limited Internal Fixation for High-Energy Tibial Plateau Fractures: Functional Results at Minimum 5-Year Follow-up

Abstract: High-energy tibial plateau fractures treated with minimal internal fixation augmented by small wire external fixation frames yielded a high percentage of cases exhibiting radiographic post-traumatic arthritis. However, because all the objectives of fracture treatment seemed to be obtained, the functional results remain satisfactory over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…[23][24][25][26] Varus/valgus alignment scoring rather than the degree of articular congruency at Rasmussen radiological scoring system probably resulted a positive correlation with the functional scores at the present study. Articular in congruency and later osteoarthritis development might affect the functional results at longer term follow-up supporting this is, Katsenis et al 27 reported deterioration of the radiological scores 5 years postoperatively compared to 3 years postoperatively while no effect at functional results could be demonstrated.…”
Section: Discussionsupporting
confidence: 49%
“…[23][24][25][26] Varus/valgus alignment scoring rather than the degree of articular congruency at Rasmussen radiological scoring system probably resulted a positive correlation with the functional scores at the present study. Articular in congruency and later osteoarthritis development might affect the functional results at longer term follow-up supporting this is, Katsenis et al 27 reported deterioration of the radiological scores 5 years postoperatively compared to 3 years postoperatively while no effect at functional results could be demonstrated.…”
Section: Discussionsupporting
confidence: 49%
“…Long-term follow-up is therefore necessary. 32 One limitation of our study was a mean follow-up period of 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted poor functional results at 3 years and radiographic arthritic changes at 4 years in patients with radiographic articular step-off greater than 4 mm. There were no excellent or good results in the four patients with varus malalignment greater than 10° [ 18 ] .…”
Section: Hybrid External Fixation With Limited Open Treatment Of the mentioning
confidence: 68%
“…Preservation of the lateral meniscus is also associated with a lower arthrosis rate and improved long-term outcomes [ 9 ] . The importance of the accuracy of the articular reduction [ 21 ] compared to a well-aligned knee [ 33 ] remains controversial, and both components [ 18 ] likely have a role in patient outcomes.…”
Section: Predicting Outcomesmentioning
confidence: 99%
See 1 more Smart Citation